2023
DOI: 10.1098/rsta.2022.0325
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new quantum trajectory molecular dynamics framework

Abstract: An extension to the wave packet description of quantum plasmas is presented, where the wave packet can be elongated in arbitrary directions. A generalized Ewald summation is constructed for the wave packet models accounting for long-range Coulomb interactions and fermionic effects are approximated by purpose-built Pauli potentials, self-consistent with the wave packets used. We demonstrate its numerical implementation with good parallel support and close to linear scaling in particle number, used for compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…However, recent research has indicated that these techniques may also be important for studying systems in equilibrium [ 122 , 123 ]. Angermeier et al [ 89 ] investigate the role non-adiabatic effects have in particle diffusion in warm dense hydrogen, while Svensson et al [ 124 ] present an extension of the wave packet description of quantum plasmas, in which non-isotropic wave packets can be elongated in arbitrary directions.…”
Section: Modelling Approachesmentioning
confidence: 99%
“…However, recent research has indicated that these techniques may also be important for studying systems in equilibrium [ 122 , 123 ]. Angermeier et al [ 89 ] investigate the role non-adiabatic effects have in particle diffusion in warm dense hydrogen, while Svensson et al [ 124 ] present an extension of the wave packet description of quantum plasmas, in which non-isotropic wave packets can be elongated in arbitrary directions.…”
Section: Modelling Approachesmentioning
confidence: 99%
“…The existence of ad hoc cutoffs and other inconsistencies within the LS-related theories encourage researchers to pursue more advanced theoretical approaches for the relaxation rates and the Coulomb logarithm. These theoretical investigations include the Molecular Dynamics (MD) simulations [13,17,[24][25][26][27][28][29][30][31] and the quantum statistical methods including the many-body Green's function approach [32], the quantum kinetic theories [32][33][34][35][36][37][38][39][40][41][42][43][44][45], the stochastic Langevinlike equation [46][47][48][49], and the method based on average-atom model [11,50]. Besides these theoretical developments, the ion-electron Coulomb logarithm was recently measured from the low-velocity energy loss experiments [12].…”
Section: Introductionmentioning
confidence: 99%